WRITING STYLE OF AGATHA CHRISTIE - N.G.Rakhimova (Лучшие интеллектуальные исследования, 2023)
Annotation: With more than 4 billion copies of her novels sold worldwide, Agatha Christie is regarded as the best-selling novelist of all time. Agatha Christie's captivating and deft writing style, which held readers' attention for more than 60 years, was what really made her a successful author. This article examines the language of most famous books, short tales, and characters written by Agatha Christie in order to assess significant aspects of her writing style. Christie created the standard for traditional Golden Age British murder mysteries with her deft use of characters and complex plotting strategies.